PENGAMBILAN KEPUTUSAN DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK MENENTUKAN PEMBELIAN MESIN TEMPEL - Chrisandy Noel Siruru; Adi Nugroho (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The decision-making system is crucial in business processes to assist decision-makers in making the right decisions. In this case, the determination of the purchase of an outboard motor is a critical decision that requires careful consideration. Therefore, the Simple Additive Weighting (SAW) method is used as a decision-making system in determining the purchase of an outboard motor. The SAW method is used to calculate the relative weight of each selected criterion and to give a value to each alternative based on the given criteria. The criteria used in determining the purchase of an outboard motor include price, brand, features, environmental waste guarantee, quality, and availability of service centers. From the normalized calculation results, Yamaha E40JMHL 40HP became the best outboard motor alternative with a score of 0.8125, and Honda BF 90 DK 2LRTD 0.575 became the less recommended alternative to be chosen for purchase.